Ancestral Tryptophan Synthase Reveals Functional Sophistication of Primordial Enzyme Complexes. Issue 6 (23rd June 2016) - Busch, Florian; Rajendran, Chitra; Heyn, Kristina; Schlee, Sandra; Merkl, Rainer; Sterner, Reinhard
Summary: Modern enzyme complexes are characterized by a high catalytic efficiency and allosteric communication between the constituting protein subunits. We were interested in whether primordial enzyme complexes from extinct species displayed a similar degree of functional sophistication. To this end, we used ancestral sequence reconstruction to resurrect the α and β subunits of the tryptophan synthase (TS) complex from the last bacterial common ancestor (LBCA), which presumably existed more than 3.4 billion years ago. We show that the LBCA TS subunits are thermostable and exhibit high catalytic activity. Moreover, they form a complex with αββα stoichiometry whose crystal structure is similar to that of modern TS. Kinetic analysis revealed that the reaction intermediate indole is channeled from the α to the β subunits and suggests that allosteric communication already occurred in LBCA TS. Graphical Abstract: Highlights: Tryptophan synthase (TS) of the last bacterial common ancestor was reconstructed α and β subunits of reconstructed TS are thermostable and catalytically active The crystal structure of reconstructed TS is similar to that of modern TS Reconstructed TS displays indole channeling and allosteric properties Abstract : Using ancestral sequence reconstruction, Busch et al. resurrect the common ancestor of all bacterial tryptophan synthases. Structural and functional characterization of this ancient αββα heterotetramer suggests that highly sophisticated enzyme complexes existed more than 3.4 billion years ago.